The Transformation of Beskap Design Elements in the Works of Indonesian Fashion Designers - Langi, Kezia Clarissa; Carolline, Grace; Marisa, Amanda (Bina Nusantara University, 2025)
The research investigates how Indonesian fashion designers incorporate elements from the beskap, a traditional Javanese shirt, into their collections. The beskap holds significant cultural importance in Indonesia and was created as a symbol of status, blending Javanese and European design features. In recent years, a growing interest in Indonesian traditional fashion has led designers to draw inspiration from the beskap for their contemporary designs. To explore this trend, the research analyzes 58 garments from three Indonesian fashion brands: KRATON, Wilsen Willim, and House of Radinindra. The research uses a design-based research method that includes image analysis, literature review, and field research conducted at the Karaton Kasunanan Surakarta Hadiningrat and Pura Mangkunegaran. The analysis focuses on several design features, including silhouette, collar, closure, garment length, sleeve length, back design, and materials. The findings reveal that key features retained in contemporary adaptations include tailored silhouettes (64%), high collars (81%), button closures (90%), elongated sleeves (83%), and distinct back openings (76%). The research concludes that these structural elements are essential for preserving cultural identity in modern fashion, serving as a reference for designers who wish to globalize traditional Indonesian clothing.